Exploring the Relations between Body Image and Self-Esteem among Two Muslim College Students in Malaysia - Abd Karim, Aishah Hanim (2015)
Background: The number of obese and overweight individuals in Malaysia has increased. Likewise, many people have becoming more interested in buying slimming and beauty products in order to become fairer and slimmer within a short period of time. The informants of the study involved two students of International Islamic University of Malaysia (IIUM). They were selected by using purposeful sampling. The study applied a qualitative method, which involved case studies and semi-structured interviews. Data gained were transcribed, analyzed, coded and categorized into similar themes. Objective: The objective of the study is to explore the college students’ definition of body image and self-esteem and their coping strategies in order to survive with their existing body images. Findings: The findings of the study included the college students’ views and understanding of body image and self-esteem, strategies in coping with their existing body image, and positive and negative personal experiences encountered due to body image. Conclusion: In conclusion, this study highlighted college students’ understanding of both body image and self-esteem. It also discussed the coping strategies used to survive with their existing body image. Some personal experiences were also shared.